Genetic characterization of hypervirulent Klebsiella pneumoniae responsible for acute death in captive marmosets - Pinpimai, Komkiew; Banlunara, Wijit; Roe, Wendi D.; Dittmer, Keren; Biggs, Patrick J.; Tantilertcharoen, Rachod; Chankow, Katriya; Bunpapong, Napawan; Boonkam, Pongthai; Pirarat, Nopadon (Frontiers in Veterinary Science, 2022)
Klebsiella pneumoniae is a Gram-negative bacterium implicated as the causative pathogen in several medical health issues with different strains causing different pathologies including pneumonia, bloodstream infections, meningitis and infections from wounds or surgery. In this study, four captive African marmosets housed in Thailand were found dead. Necropsy and histology revealed congestion of hearts, kidneys and adrenal glands. Twenty-four bacterial isolates were obtained from these four animals with all isolates yielding identical phenotypes indicative of Klebsiella pneumoniae based on classical identification schema. All the isolates show the susceptibility to amikacin, cephalexin, doxycycline, gentamicin, and enrofloxacin with intermediate susceptibility to amoxycillin/clavulanic acid. One isolate (20P167W) was chosen for genome analysis and determined to belong to sequence type 65 (ST65). The genome of 20P167W possessed multiple virulence genes including mrk gene cluster and iro and iuc gene cluster (salmochelin and aerobactin, respectively) as well as multiple antibiotic resistance genes including blaSHV-67, blaSHV-11, oqxA, oqxB, and fosA genes. This isolate has a close genetic relationship with isolates from humans in Ireland, but not from Thailand and California sea lions. Phylogenetic studies using SNP show that there was no relation between genetic and geographic distributions of all known strains typing ST65, suggesting that ST65 strains may spread worldwide through multiple international transmission events rather than by local expansions in humans and/or animals. We also predict that K. pneumoniae ST65 has an ability to acquire genetic mobile element from other bacteria, which would allow Klebsiella to become an even greater public health concern.